Pelestarian Kuliner Lokal Melalui Olahan Limbah Biji Durian untuk Meningkatkan Kesejahteraan Unit Usaha Kecil di Desa Makmur Kecamatan Binjai - Ganie, Rohani; Nasution, Ikhwanuddin; Gustanto, Gustanto; Syahputra, Fikry Prastya (Jurnal Pengabdi, 2024)
The target of community service is Unit Usaha Kecil "Keripik Kue Bawang Susi" located in Makmur Village, Binjai District. Problems: 1. Lack of knowledge and skills of human resources in creatively developing product varieties, 2. Simple and unattractive packaging design, 3. Lack of equipment to support work processes, 4. Limited knowledge in utilizing social media, 5. Partners not knowing how to contact relevant agencies for guidance and development. Service Objectives: increase the knowledge and skills of partner human resources in creatively developing varieties of processed durian seed waste products, developing packaging designs, equipping work process support equipment, increasing knowledge in using social media for product promotion, building net-working with several agencies/corporates to obtain coaching and development. The methods used to increase knowledge are outreach with creative economy materials, local culinary preservation and product development design. Increasing skills through training/mentoring methods for partner human resources regarding creativity in developing product varieties, optimizing the use of digital platforms for promotional media. Measuring increased knowledge through pre-test and post-test. The results of the activity show the average percentage increase in Business Unit knowledge in the good category, the average percentage of skill increase targets in the good category. The impact of the service activities is to make the Unit Usaha Kecil "Keripik Kue Bawang Susi"   have a variety of products using processed durian seed waste based on local culinary delights.